Global Burden of Allergies: Mechanisms of Development, Challenges in Diagnosis, and Treatment - Ewa Alska; Agata Doligalska; Katarzyna Napiórkowska-Baran; Marcin Dolina; Karolina Osińska; Anastazja Pilichowicz; Aleksandra Wojtkiewicz; Justyna Julia Kaczor; Bartłomiej Szymczak; Zbigniew Bartuzi (Life)
Allergic diseases represent a major and growing global health concern, with increasing prevalence among both children and adults. This manuscript presents an extensive review of allergy mechanisms, epidemiology, diagnostics, and clinical challenges, highlighting the complex interplay between immune system dysregulation and environmental exposures. The authors provide a structured analysis of hypersensitivity types, with particular focus on IgE-mediated responses, and emphasize the role of immune barrier defects, epigenetics, and the microbiota in allergic pathogenesis. This manuscript explores diagnostic limitations, including test sensitivity, specificity, and the presence of hidden allergens, as well as challenges in identifying food-related or atypical allergic reactions. A novel and valuable aspect is the discussion of allergy as a potential clinical manifestation of primary immunodeficiencies, such as selective IgA deficiency, Wiskott–Aldrich syndrome, hyper-IgE syndrome, and Netherton syndrome. This review also outlines challenges in treatment, especially among polysensitized patients, and examines the psychosocial burden and complications of allergic diseases, including mental health, nutritional deficiencies, and impaired sleep. This comprehensive synthesis underscores the need for early diagnosis, multidisciplinary management, and personalized therapeutic strategies to improve quality of life of allergic patients.